2020
DOI: 10.1007/s40291-020-00490-7
|View full text |Cite
|
Sign up to set email alerts
|

More than a Genetic Code: Epigenetics of Lung Fibrosis

Abstract: At the end of the last century, genetic studies reported that genetic information is not transmitted solely by DNA, but is also transmitted by other mechanisms, named as epigenetics. The well-described epigenetic mechanisms include DNA methylation, biochemical modifications of histones, and microRNAs. The role of altered epigenetics in the biology of various fibrotic diseases is well-established, and recent advances demonstrate its importance in the pathogenesis of pulmonary fibrosis—predominantly referring to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 141 publications
0
18
0
Order By: Relevance
“…), the level of surfactant protein C (Sp-C), the activation and proliferation of fibroblasts are all significantly affected. Additionally, histone modifications can also affect the anti-apoptotic ability of fibroblasts by inhibiting anti-fibrotic genes such as FAS and caveolin 1 (Cav-1) ( Bartczak et al, 2020 ). Ligresti,G et al identified that histone methyltransferase G9a/chromobox homolog 5 (CBX5)/methylated lysine 9 residue on histone 3 (H3K9me) were key regulators of fibroblast activation, and determined that by participating in the CBX5/G9a pathway, TGFβ and increased matrix stiffness effectively inhibited PGC1α expression in lung fibroblasts ( Ligresti et al, 2019 ).…”
Section: Risk Factorsmentioning
confidence: 99%
“…), the level of surfactant protein C (Sp-C), the activation and proliferation of fibroblasts are all significantly affected. Additionally, histone modifications can also affect the anti-apoptotic ability of fibroblasts by inhibiting anti-fibrotic genes such as FAS and caveolin 1 (Cav-1) ( Bartczak et al, 2020 ). Ligresti,G et al identified that histone methyltransferase G9a/chromobox homolog 5 (CBX5)/methylated lysine 9 residue on histone 3 (H3K9me) were key regulators of fibroblast activation, and determined that by participating in the CBX5/G9a pathway, TGFβ and increased matrix stiffness effectively inhibited PGC1α expression in lung fibroblasts ( Ligresti et al, 2019 ).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Pulmonary fibrosis (PF) includes more than 200 different pathological conditions characterized by inflammation and scar tissue formation in the lungs. PF can be grouped in five categories: drug-induced, radiation-induced, environmental, autoimmune, and occupational ( 1 ). However, the most common type of PF is represented by the “Idiopathic Pulmonary Fibrosis” (IPF), whose etiology remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs have been associated with almost every stage in the pathogenesis of IPF including lung epithelial repair; epithelial–mesenchymal transition (EMT) such as let-7d, miR-200, miR-26a, and miR-375; activation of fibroblast and their trans differentiation to myofibroblasts such as miR-21, miR-155, miR-26a, miR-27a-3p, miR-9-5p; AECII cell senescence; and regulation of collagen production such as miR-320a [ 116 , 117 , 118 ]. MicroRNAs are both upregulated and downregulated during the pathogenesis of IPF and were shown to have both pro-fibrotic and anti-fibrotic roles in the pathogenesis of the disease [ 119 ]. Interestingly a study identified 47 significantly differentially expressed serum miRNAs from IPF patients compared with healthy controls including 21 upregulated miRNAs and 26 downregulated miRNAs [ 120 ].…”
Section: Epigenetic Dysregulation In Ipf and Copdmentioning
confidence: 99%